Mechanisms of Modulation of Ferroptosis and Its Role in Central Nervous System Diseases - Tan, Qingyun; Fang, Yuying; Gu, Qiong (Frontiers in Pharmacology, 2021)
Ferroptosis is a new form of programmed cell death characterized by intracellular iron-dependent accumulation of lipid peroxide and primarily associated with iron metabolism, glutathione-dependent pathway, and coenzyme Q10-dependent pathway. Recent studies demonstrate that ferroptosis is associated with central nervous system (CNS) diseases, such as stroke, Parkinson's disease, Alzheimer's disease, and Huntington's disease. This review summarizes the key regulatory mechanisms of ferroptosis and its role in CNS diseases. These updates may provide novel perspective for the development of therapeutical agents against CNS diseases.